Penguatan Kompetensi Reflektif Mahasiswa PPG melalui Focus Group Discussion pada Praktik Pembelajaran Terbimbing - Dina Ramadhanti; Defril Syafrin; Wiranti Gusman (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2026)
Reflective competence is one of the important skills that must be possessed by Professional Teacher Education (PPG) students to improve the quality of teaching practice. However, student reflection on learning practice still tends to be descriptive and does not demonstrate in-depth self-evaluation skills. This community service activity aims to strengthen PPG students' reflective competence through Focus Group Discussions (FGDs) on guided learning practices. The activity was carried out with five PPG students majoring in Indonesian Language at SMP Negeri 7 Padang during three cycles of guided learning practices. The methods used included reflection mentoring, FGD implementation, providing feedback by the supervising lecturer and mentor teacher, and ongoing reflection in each cycle. Data obtained from reflection worksheets from Cycles 1, 2, and 3 were analyzed descriptively. The results of the activity showed an increase in the quality of student reflection, especially in the aspects of learning analysis, identification of obstacles, self-evaluation, and follow-up planning. In the first and second cycles, student reflections were still predominantly descriptive, while in the third cycle students were able to conduct more analytical and critical reflections on the learning practices implemented. Thus, FGDs proved effective in strengthening PPG students' reflective competence and can be used as a mentoring strategy in guided learning practices.